2012
DOI: 10.1016/j.ssci.2011.09.015
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on multi-vehicle motorcycle crashes using log-linear models

Abstract: Motorcyclists are the most crash-prone road-user group in many Asian countries including Singapore; however, factors influencing motorcycle crashes are still not well understood. This study examines the effects of various roadway characteristics, traffic control measures and environmental factors on motorcycle crashes at different location types including expressways and intersections. Using techniques of categorical data analysis, this study has developed a set of log-linear models to investigate multi-vehicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 39 publications
(52 reference statements)
0
32
0
Order By: Relevance
“…Driver failure to see two-wheelers, difficulty in determining motorcycle speeds, and reduced conspicuity of two-wheelers have been identified as important causes of 'failure to give way' type crashes in many studies (e.g., Haque et al, 2012;Horswill et al, 2005;Pai, 2011b;Pai et al, 2009). While driver attention is important, improving conspicuity of riders by using illuminated lights, wearing reflective clothing, and using retro-reflective marking on helmets and two-wheelers could potentially improve rider safety.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Driver failure to see two-wheelers, difficulty in determining motorcycle speeds, and reduced conspicuity of two-wheelers have been identified as important causes of 'failure to give way' type crashes in many studies (e.g., Haque et al, 2012;Horswill et al, 2005;Pai, 2011b;Pai et al, 2009). While driver attention is important, improving conspicuity of riders by using illuminated lights, wearing reflective clothing, and using retro-reflective marking on helmets and two-wheelers could potentially improve rider safety.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller size and less intensity of bicycle lights could explain why drivers failed to give way to bicyclists more often at night than motorcyclists. Increasing the conspicuity of riders and two-wheelers to improve safety has been recommended in a number of studies (Haque et al, 2012;Pai et al, 2009;Thornley et al, 2008;Wood et al, 2009;Yuan, 2000). In addition to headlight (static or blinking), reflective vest, and reflective markings on two-wheelers, researchers (Wood et al, 2012) have suggested use of ankle and knee reflectors for bicyclists.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations